The story of the open pension funds and the employee capital plans in Poland: Will it succeed this time? - Barbara Błaszczyk (Center for Social and Economic Research (CASE), 2020)
Poland's new Employee Capital Plans (PPK) scheme, which is mandatory for employers, started to be implemented in July 2019. The article looks at the systemic solutions applied in the programme from the perspective of the concept of the simultaneous reconstruction of the retirement pension system. The aim is to present arguments for and against the project from the point of view of various actors, and to assess the chances of success for the new system. The article offers a detailed study of legal solutions, an analysis of the literature on the subject, and reports of institutions that supervise pension funds. The results of this analysis point to the lack of cohesion between certain solutions of the 1999 pension reform and expose a lack of consistency in how the reform was carried out, which led to the eventual removal of the capital part of the pension system. The study shows that additional saving for old age is advisable in the country's current demographic situation and necessary for both economic and social reasons. However, the systemic solutions offered by the government appear to be chiefly designated to serve short-term state interests and do not create sufficient incentives for pension plan participants to join the programme.
Keywords: G28; G41; H55; J32; 330; pension system; public pension regulation; private pension saving plans; employee pension funds; Employee Capital Plans